Role of Multidetector Computed Tomography in Evaluation of Ovarian Lesions in Women Clinically Suspected of Malignancy - Mukhtar, Shazia (Asian Pac J Cancer Prev, 2017)
OBJECTIVE: To determine the diagnostic accuracy of multidetector computed tomography (MDCT) in the evaluation of ovarian carcinoma using histopathology as the gold standard. METHODS: This prospective cross-sectional study was conducted at Department of Radiology, Dow international medical college, DUHS, Karachi from December 2015 to April 2016. All patients of 30-60 years of age who were referred for CT a scan of the abdomen and pelvis with clinical suspicion of malignant ovarian cancer were included. A total of 158 cases were assessed with signs and symptoms of weight loss and an abdominal or pelvic mass detected on examination by a physician. RESULTS: The mean age was 42.7 ±10.3 years (range 30-60). The largest group (46, 29.1%) presented with Stage 0 disease. The mean duration of symptoms was 4.06 ±1.39 months (range 1-6). Taking histopathology as the gold standard the sensitivity, specificity, NPV, PPV and overall diagnostic accuracy values for MDCT were 95.6%, 97.3%, 93.5%, 97.3% and 96.8%, respectively. CONCLUSION: MDCT showed high accuracy in differentiating benign and malignant lesions and as well as staging of malignant cases which should be very helpful in management of ovarian disease.